1966
DOI: 10.1039/tf9666200987
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of micellization of alkylsulphinylalkanols

Abstract: The thermodynamics of micellization of a new series of non-ionic surface-active agents, the alkylsulphinylalkanoIs (RSO(CH2),OH), has been examined. It has been shown that the behaviour of methylene groups in close proximity to the hydrophilic groups is very different from those further removed. Thus, additional methylene groups in the alkyl chain remote from the head group give a decrease in enthalpy which accounts almost entirely for the decrease in free energy, while additional methylene groups between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1
1

Year Published

1966
1966
1992
1992

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 0 publications
2
7
1
1
Order By: Relevance
“…Assuming 0 corresponds to the bulk value of -50 ergs/cm2 we obtain for A a value of 10 &/CHz. This is of the correct order since the total increment in surface area per methylene group for the monomer is [15][16][17][18][19][20] &. 22 When the maximum hydrocarbon/water interface is eliminated, with the hydrophilic groups completely covering…”
Section: Discussionmentioning
confidence: 99%
“…Assuming 0 corresponds to the bulk value of -50 ergs/cm2 we obtain for A a value of 10 &/CHz. This is of the correct order since the total increment in surface area per methylene group for the monomer is [15][16][17][18][19][20] &. 22 When the maximum hydrocarbon/water interface is eliminated, with the hydrophilic groups completely covering…”
Section: Discussionmentioning
confidence: 99%
“…OH (n = 2,3,4) were prepared from pure n-octyl mercaptan by the method previously described. 6 No minima were observed in the surface tension against log concentration plots of aqueous solutions at the critical micelle concentrations (c.m.c.) which were 0.50 g/lOO ml at 25°C for all three compounds.…”
Section: Methodsmentioning
confidence: 99%
“…The understanding of the thermodynamics of micelle form ation is of much theoretical and practical importance.Even though a great many studies on the thermodynamics of micelle formation have been reported in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), the data available are not completely consistent. The purpose of this study is to report on the current theories and to comment on the data reported in the literature on the thermodynamics of micelle formation.…”
Section: Introductionmentioning
confidence: 94%